2015
DOI: 10.3823/1747
|View full text |Cite
|
Sign up to set email alerts
|

High Microbiological Spectrum Resistance Rates in urine isolates from Jalisco, Mexico. A retrospective study and literature review

Abstract: Background: Urinary tract infections (UTIs) are a major public health problem worldwide. In Latin America, most UTIs are treated without bacteriological identification. Our aim was to examine resistance rates to commonly prescribed antibiotics, focusing on cases from Jalisco, Mexico; and additionally to conduct a review of the literature to search for resistance patterns in other countries of Latin America. Methods: Results:We obtained 1.206 consecutive samples from outpatient and inpatient facilities, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Main pathogens responsible for community-acquired uncomplicated UTIs were E. coli and ESBL-E. coli; however, the number of cases from the latter was lower compared to our own previously published findings (25% versus 68%) [11].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Main pathogens responsible for community-acquired uncomplicated UTIs were E. coli and ESBL-E. coli; however, the number of cases from the latter was lower compared to our own previously published findings (25% versus 68%) [11].…”
Section: Discussioncontrasting
confidence: 78%
“…Common uropathogens that cause community-associated UTIs include Escherichia coli (E. coli), Klebsiella pneumoniae, and Enterococci, with the first being the primary causative agent (80%) in most studies [8]. Furthermore, among E. coli isolates, it has been found that from 1.6% to 3.9% are producers of extended spectrum-beta lactamases (ESBLs) in outpatient settings reported in France and the United States, respectively [9,10], and in our own previous experience, but with a different approach, ESBLs can be found in up to 69.5% in the outpatient setting [11].…”
Section: Introductionmentioning
confidence: 86%